EVALUATION OF HYPOLIPIDEMIC ACTIVITY OF OPUNTIA ELATIOR FRUIT JUICE IN HIGH-FAT DIET-INDUCED HYPERLIPIDEMIA IN WISTAR ALBINO RATS - HEMANGI AMRUTBHAI VIRANI; MITUL SANJAYBHAI UPADHYAY; PIYUSH MANSINH PARGI; ASHISH P. ANOVADIYA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Evaluate the hypolipidemic activity of Opuntia elatior fruit juice (OFJ) in normal diet and high-fat diet-fed Wistar albino rats by plasma lipid profiles and compare it with atorvastatin. Assess the effect of O. elatior (OE) and atorvastatin on lipid accumulation in the liver by histopathological examination. Methods: Hyperlipidemia was produced in rats by feeding them with cholesterol powder (2%) mixed with butter (10%). A total of six groups, six rats per group, divided into normal control (NC), disease control (DC), active control (AC), extract control, test group 1 (low-dose [LD] herb 5 mL/kg), and test group 2 (high-dose [HD] herb 10 mL/kg). Estimation of lipid profile levels, serum urea, and serum creatinine was done at different time intervals. OFJ was used at two different doses of 5 ml/kg (LD) and 10 ml/kg (HD) in test groups. At the conclusion of the experiment, the animals were euthanized in accordance with ethical guidelines, and liver tissues were collected for histopathological analysis. Results: At both 5 mL/kg and 10 mL/kg doses, OFJ showed a significant reduction (p<0.05) of total cholesterol, triglycerides (TG), very low-density lipoprotein (VLDL), and low-density lipoprotein and an increase in high-density lipoprotein when compared with DC group at the end of 8th week. The HD group showed more reduction in VLDL and TG than the AC group. Conclusion: OE showed hypolipidemic activity.